Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1757-7861.2012.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Gunshot Femoral Fractures with Vascular Injury: A Retrospective Analysis

Abstract: Surgical sequence did not appear to impact the outcome with regard to limb loss, compartment syndrome, or mortality. Orthopaedic repair following vascular repair, however, is a risk for disruption of the vascular repair. We suggest that close and early direct communication between the orthopaedic and vascular surgeons take place in order to facilitate a satisfactory outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Several investigations at the authors' institution have concluded that either approach is acceptable in the appropriate patient, and that an early discussion between the vascular and orthopedic teams facilitates the best outcome. 36,37 If the vascular team anticipates the need for stabilized length and the orthopedic procedure can be completed quickly, the orthopedic team may proceed. On the other hand, if limb ischemia appears to be threatening the limb, the vascular repair should take priority.…”
Section: Vascular Injurymentioning
confidence: 99%
“…Several investigations at the authors' institution have concluded that either approach is acceptable in the appropriate patient, and that an early discussion between the vascular and orthopedic teams facilitates the best outcome. 36,37 If the vascular team anticipates the need for stabilized length and the orthopedic procedure can be completed quickly, the orthopedic team may proceed. On the other hand, if limb ischemia appears to be threatening the limb, the vascular repair should take priority.…”
Section: Vascular Injurymentioning
confidence: 99%
“…47 Although it is a common practice to proceed directly with vascular repair initially, some studies have challenged this notion and showed that temporary intravascular shunts may improve patient morbidity and decrease the risk of compartment syndrome. 5 In a study of 24 patients with ballistic femur fractures and an associated vascular injury, Rehman et al 48 showed that surgical sequence did not seem to affect the outcome regarding limb loss, compartment syndrome, or mortality. They did find, however, that orthopaedic intervention after revascularization is a risk for disruption of the vascular repair.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a tourniquet will compromise the collateral perfusion that is likely responsible for continued distal perfusion in cases of major arterial injury [28]. The surgical sequence of events, "fracture first" or "vascular first, " is somewhat controversial [29][30][31]. We prefer to proceed with rapid external fixation prior to vascular repair to protect future repair.…”
Section: A a B B C C D D E Ementioning
confidence: 99%